2020
DOI: 10.1002/acr.23929
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Spinal Mobility in Ankylosing Spondylitis: A Repeated Cross‐Sectional Study

Abstract: ObjectiveTo evaluate the course of impaired spinal mobility in patients with long‐standing well‐defined ankylosing spondylitis (AS).MethodsData from 232 patients with AS (186 men, 46 women) and 3,849 clinical measurements performed between February 1980 and June 2016 were analyzed. Lateral spinal flexion (LSF), the 10‐cm Schober test, chest expansion (CE), and cervical rotation measurements were stratified by disease duration at 10‐year intervals and compared with published age‐ and height‐adjusted spinal mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Also, although a randomization was used to assign the patients to each group, the inhomogeneity of gender within the groups could have influenced the present outcomes. In addition, impairment of spinal mobility is known to be dependent on the course of the disease in AS (Sundstrom et al, 2019). Thus, a better control of gender homogeneity and disease duration by stratification should be taken into account for providing data consistency in future studies.…”
Section: Limitationsmentioning
confidence: 99%
“…Also, although a randomization was used to assign the patients to each group, the inhomogeneity of gender within the groups could have influenced the present outcomes. In addition, impairment of spinal mobility is known to be dependent on the course of the disease in AS (Sundstrom et al, 2019). Thus, a better control of gender homogeneity and disease duration by stratification should be taken into account for providing data consistency in future studies.…”
Section: Limitationsmentioning
confidence: 99%
“…These changes in postural control and balance can negatively affect patients' participation in daily life and increase their risk of falling. Sundström et at also reported that spinal mobility decreases with increasing disease severity and age [15]. Kuo et al…”
Section: Discussionmentioning
confidence: 93%
“…As part of the treatment routine, the patients are also offered rehabilitation when needed, and during these periods, measurements are performed at enrollment and on completion of rehabilitation. At the department, 232 patients with a verified diagnosis of AS according to the modified New York criteria (20) and with a known time point of onset of AS symptoms were identified by examining medical records as previously described (17). In these 232 individuals, at least 1 visit with spinal mobility measurements was registered between February 1980 to June 2016.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of age on spinal mobility is considerable, and using regression models, Ramiro et al developed reference centile charts of the progressive age‐related decline in spinal mobility among individuals without spinal impairment (16). We have previously compared these norm data with those of a large AS study population to describe characteristics over a disease span of 40 years using repeated cross‐sectional analyses (17), and also to define predictors of abnormal spinal mobility (18). Based on the assumption of a linear development of spinal mobility impairment at a group level in AS, we can further understand the content of our data through extended analyses of linear regression models.…”
Section: Introductionmentioning
confidence: 99%